POTENSI DAN KEKUATAN KECERDASAN PADA MANUSIA (IQ, EQ, SQ) DAN KAITANNYA DENGAN WAHYU - Ahmad, Askar (State Institute of Islamic Studies (IAIN) Palu, 2006)
Current finding indicates that in humans there exist some potencies, that is intellectual quotient (IQ), emotional quotient and spiritual quotient (SQ). Intellectual quotient serves as a quotient in logics and mathematics as well as other sciences, centered on the left brain. Emotional quotient serves as a social quotient, in establishing relationship with others and in building an empathy, centered on the right brain. Spiritual quotient (SQ) serves as a quotient lies on how to find the meaning of life. In the Qur’an we find some verses elucidating those human quotients such as ,aql, qalb, ruh dan nafs. Whenever the three human potencies, ruh, aql, dan qalb work well, they will result in perfect humans, but whenever nafs dominates the three potencies, it will result in evil humans. Kata Kunci : Kecerdasan intelektual, kecerdasan emosional, kecerdasan spiritual, aql , qalb , ruh , nafs